(untitled) (Research, Society and Development, 2021)
Introduction: Mucocele is a common benign lesion of the oral mucosa that originates from salivary glands. The term refers to a cavity containing mucus in its interior, since the term “cele” comes from the Greek “kele” which can mean hernia or swelling, being especially used to name empty cavities. Objective: The objective of this work is to report a clinical case of labral mucocele in a 2-year-old child, removed by total surgical excision of the lesion. Case report: Female patient, leucoderma, attended the Pediatric Dentistry clinic of Centro Universitário Tiradentes - UNIT. The mother reported at the time of the consultation that, about 30 days ago, a “ball” appeared in the child’s lower lip, which hurt when she was eating. On clinical examination, a bullous lesion was observed, with clear limits, approximately 10 mm in diameter, fibrous consistency, sessile-based mould, normochromic coloration, with characteristics similar to those of a mucocele. Surgical excision of the lesion was performed and the collected material was fixed in 10% formalin and sent for histopathological examination. Afterwards, postoperative guidelines were recommended, as well as care at the site of the injury and prescription of analgesics. The result of the histopathological examination confirmed the diagnosis of a mucus retention cyst (mucocele). Conclusion: Mucocele is the most common lesion in young patients and presents characteristic pathognomonic signs. Among the various therapeutic techniques, conservative surgical treatment is still the most used technique, proving to be an effective, simple approach with a good prognosis.